Synthesis, Crystal Structure, and Theoretical Studies of N-(4-((4-chlorobenzyl)oxy)phenyl)-4- (trifluoromethyl)pyrimidin-2-amine - Jian-Chang Jin; Zhao-Hui Sun; Ming-Yan Yang; Jing Wu; Xing-Hai Liu (Journal of Chemistry)
The title compound (C18H13ClF3N3O) were synthesized and recrystallized from CH3OH. The compound was characterized by H1 NMR, MS, HRMS, and X-ray diffraction. The compound crystallized in the monoclinic space group P2(1)/n with a=8.2354 (14), b=12.686 (2), c=16.633 (3) Å, α=90, β=97.951 (3), γ=90∘, V=1721.0 (5)  Å3, Z=4, and R=0.0376 for 1933 observed reflections with I>2σ(I). X-ray analysis reveals that intermolecular N–H⋯N interactions exist in the adjacent molecules. Theoretical calculation of the title compound was carried out with HF/6-31G (d,p), B3LYP/6-31G (d,p). The full geometry optimization was carried out using 6-31G (d,p) basis set and the frontier orbital energy. The optimized geometric bond lengths and bond angles obtained by using HF and DFT (B3LYP) showed the best agreement with the experimental data.